Development of AKM Numeracy Instruments on Numbers, Geometry & Measurement Materials for Grade IV Elementary School Students - Mufidah, Imroatul; Kusairi, Sentot; Arifin, Slamet (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
The results of the PISA Study show that students' numeracy abilities are still below average. So far, students' knowledge is still focused on the concept of counting, without knowing the usefulness and benefits of mathematical concepts in everyday life. This study aimed to develop and validate the AKM numeracy instrument on numbers, geometry, and measurements for Grade IV elementary school students. This research uses the type of Â Research and Development (R&D) development research, using the ADDIE model which has 5 stages, namely Analyze, Design, Development, Implementation, and Evaluation. The data collected is data on students' numeracy abilities obtained through testing the AKM instrument on numeracy on numbers, geometry, and measurements specifically for 4th-grade elementary school students. Data content validity, empirical validity, and reliability that has been collected was analyzed by content validity (Gregory, 2000), Product Moment, and Cronbach's Alpha. The results of the assessment of the two validators shows that the numearcy AKM instrument is categorized as having a high validity of 0.70. Based on the results of the descriptive statistical analysis of the Numeracy AKM test, it is known that the mean value is 88, whil minimum numeracy score is 48, and the maximum score is 100 with a standard deviation of 13.81. The reliability test results that the value of rcount > rtable is 0.949 > 0.423. Thus, it can be concluded that the developed numeracy test instrument is valid or has high reliability and can be used to collect research data related to student numeracy.Keywords: Instrument Development Numeracy, Minimum Competency Assessment (AKM)